2020
DOI: 10.1038/s41598-020-79283-1
|View full text |Cite
|
Sign up to set email alerts
|

Promising candidates for extracorporeal cardiopulmonary resuscitation for out-of-hospital cardiac arrest

Abstract: Precise criteria for extracorporeal cardiopulmonary resuscitation (ECPR) are still lacking in patients with out-of-hospital cardiac arrest (OHCA). We aimed to investigate whether adopting our hypothesized criteria for ECPR to patients with refractory OHCA could benefit. This before-after study compared 4.5 years after implementation of ECPR for refractory OHCA patients who met our criteria (Jan, 2015 to May, 2019) and 4 years of undergoing conventional CPR (CCPR) prior to ECPR with patients who met the criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Increase in population, urbanization, demand for expanded agriculture, modernized living standards have increased the demand for water 1 . Water is a renewable resource, and it is transferred between the ocean, atmosphere, and the land (through rainfall) 2 . Rainfall is a life-sustaining water resource, and its variability influences the water availability across any region.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in population, urbanization, demand for expanded agriculture, modernized living standards have increased the demand for water 1 . Water is a renewable resource, and it is transferred between the ocean, atmosphere, and the land (through rainfall) 2 . Rainfall is a life-sustaining water resource, and its variability influences the water availability across any region.…”
Section: Introductionmentioning
confidence: 99%
“…However, determining optimal threshold in practice is challenging. Although we dichotomised no-flow time based on the previous studies and real-world practice for initiating ECPR,4–6 the indication for ECPR remains unestablished. Moreover, the optimal threshold depends on the situation where the marker is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Because ECPR requires considerable resources, current recommendations suggest using ECPR for selected patients who have the best chances of successful outcomes. Although the indication criteria have not been established, a criterion for no-flow time of <5 min or <10 min has been proposed 4–6. However, estimating the no-flow time is uncertain in unwitnessed OHCAs which account for 33.3%–55.1% of OHCA cases 7–9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies reported that E‐CPR may improve survival and neurological outcomes in patients with OHCA when compared to C‐CPR 9–13 . However, other studies showed small or no effect on survival and systematic reviews conducted on the topic yielded contrasting results 14,15 .…”
Section: Introductionmentioning
confidence: 99%